PENERAPAN KOMUNIKASI PERSUASIF DALAM PROSPEK BUSINESS OPPURTUNITY ANGGOTA KANGZEN KENKO INDONESIA - Bramantawira, Kristiardi (Universitas Negeri Surabaya, 2023)
The limitations of face-to-face meetings during the pandemic period from 2020 to early 2022 prompted the acceleration of digitization in the system for recruiting new members and selling products. Kangzen Kenko Indonesia is an example of a company implementing a network business in Indonesia that intensively holds webinars to recruit new members. In the recruitment process, Indonesian KK members must apply persuasive communication to prospective new members. This study uses a qualitative approach and uses a descriptive type. The research method used is phenomenology. The results of the study show that persuasive communication is carried out on social media by building personal branding and intimacy through visual content uploaded via social media, regularly holding webinars by providing testimonials and attractive offers for prospects on an ongoing basis which makes KK products more existent with others. With these findings, it is hoped that further research will emerge that discusses this further.